Tension-type headache and low back pain reconsidered - Astrup, Jens; Gyntelberg, Finn (Frontiers in Neurology, 2022)
The natural history and clinical course of tension-type headache and non-specific low back pain are reconsidered. By closer examination these two conditions appear to share a number of specific clinical features. Both are muscular pain conditions along the spine, they have a female preponderance, they may occur spontaneously or follow a trivial traumatic incident and they both have a high risk of chronicity. The affected muscles are tender with tender points. EMG indicates diffuse hyperactivity and abnormal activation pattern, and motor control of the affected muscles and of adjacent muscle groups is dyscoordinated. These shared features suggest an analogous pathophysiology involving the neuromotor control of affected and adjacent muscle groups in the cervical and the lumbar regions respectively. As recently suggested for the whiplash disease we suggest the term spinal dyssynergia for this specific pattern of pathology. This suggestion provides a new perspective for the understanding of these diseases by placing their cause within the central nervous system and not in the spine or spinal musculature. This perspective warrants further clinical, neurophysiological and neuropharmacological studies of this ‘family’ of common but yet poorly understood clinical muscular pain conditions along the spine.